Carbon Stored in the Arboreal Stratum of Livestock and Natural Systems of the Municipality of Albania, Caquetá, Colombia - Rojas-Vargas, Erika Paola; Silva-Agudelo, Edgar Daniel; Guillén-Motta, Ana Yiceth; Motta-Delgado, Pablo Andrés; Herrera-Valencia, Wilmer (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The aim of this study was to calculate the carbon storage capacity in the arboreal stratum of five land uses, both in livestock systems as natural: a) traditional pastures with scattered trees in low-density (PT), b) improved pastures with scattered trees in low-density (PM), c) silvopastoral systems in high-density (SSP), d) native forest (Bo) and e) natural regeneration (RN). Three replicates for land use were performed and recorded each tree within the floristic inventory; for PT, PM and SSP plots of 1000 m2 were made, for Bo plots of 2000 m2 and for natural regeneration plots of 1000 m2 for identification of seedlings, saplings and poles. Data were examined using analysis of variance and compared by the DGC test to a significance level of 95 %. The forest showed significant differences with values of 249.035 Mg ha-1 in biomass and carbon 124.517 Mg ha-1 with respect to other land uses; the variable diameter to the breast height (DBH) revealed significant differences (p<0.05), where natural regeneration obtained the lowest DBH while native forest the highest with 4.93 and 18.52 cm, respectively. The number of individuals (tree ha-1) was not significantly different between native forest (525) and natural regeneration (930), but these two showed significant differences as regard to agroecosystems of pastures, with values of 17, 47 and 207 individuals ha-1 for PM, PT and SSP respectively. In conclusion, it was noted that coverage with the highest capacity for biomass production and carbon storage was the forest and the lowest were improved pastures with Brachiaria sp species, in addition, the highest density of trees arose in the coverage of natural regeneration, which have a high potential for increasing carbon sequestration capacity.